Motivating intention to take action on behalf of an out-group: implications for the use of advocacy messages in social marketing strategies. Issue 11 (24th July 2017) - Summers, Jane; Summers, Jessica
ABSTRACT: In psychological research, the Social Identity Theory has been used to explain people's motivation to take action in support of causes predominantly with a focus on in-group action. This study takes up the call to extend the limited attention given to intent-to-act on behalf of an out-group. Our research investigates support for the legalisation of medical marijuana (an out-group) and concludes that message structure is critical to increasing the likelihood of intent-to-act in support of an out-group. Specifically, we show that messages delivered from a legitimate advocate for the issue will generate empathy towards those affected and anger towards the perceived injustice, motivating intent to take action. Social marketers, charged with engaging communities to support programmes targeted at disadvantaged minority groups within the population, will benefit from the results of this research.